The Influence of Social Media on the Behavior of Teenagers at SMK Bina Satria Medan - Dahri Yani Hakim Tanjung; Sri Lestari Rahayu (STMIK Pontianak, 2021)
Broadly speaking, social media can be said as an online media, where users (users) can share, participate, and create accounts in the form of blogs, forums, and social networks using internet-based applications supported by information technology to create virtual world spaces. The emergence of various kinds of social media has a direct influence, both positive and negative. For vocational students who belong to the category of teenagers, they are part of social media users with a high percentage level. Because adolescence is a period of transition from children so that curiosity is very high, it is possible that social media can become an addiction so that they lose time for other more important activities. There is a lot they can see and get from using social media, whether it's social media or social media. positive and not a little negative that they can imitate so that there are many impacts resulting from the use of social media for teenagers without direct monitoring from family or parents. Therefore, with this training, it can provide insight and knowledge to students that social media has a major influence on the development of adolescent behavior so that they can manage their time and themselves in using social media so as not to reduce enthusiasm and student learning achievements to continue to achieve their goals. his wish.